تطبيق طريقة المناقشة الجماعية الصغيرة ( ) لترقية نشات الطلاب في تعليم اللغة العربية لطلاب الصف السابع بمدرسة دار العلم الثانوية الأهلية باتانج كويس - Ginting, Mita Atiiqah br; Sihombing, Fahrurrozi (STAI Ali bin Abi Thalib Surabaya, 2025)
This research is designed to improve the Arabic language learning activity of 7th-grade students at MTs Darul Ilmi Batang Kuis for the 2025-2026 academic year. The type of research is Classroom Action Research (PTK). The research design for this study uses multiple Siklus, namely Siklus I, II, and so on, and has four stages: planning, implementation, observation, and reflection. The subjects of this study were the students of class VII-2 at MTs Darul Ilmi Batang Kuis, totaling 32 students. The data collection techniques used in this study are observation, questionnaires, and tests. The background of this research is that many students are not serious during Arabic language learning. They prefer to talk to their friends rather than listen to instructions from their teacher. Additionally, there are also students who are shy or even afraid to express their opinions. Thus, there needs to be improvement in both the Arabic language learning process, especially in the methods used. The results of this study indicate an increase in the learning activity of 7ṭ-grade students at MTs Darul Ilmi Batang Kuis. The percentage increase was from 42% in Siklus I to 79% in Siklus II. Additionally, there was an increase in the average test scores from 71.32 in Siklus I to 85 in Siklus II. The findings are consistent with the theory that the Small Group Discussion method is able to increase student activity in learning Arabic. As explained earlier, this method is able to encourage students to be more courageous in expressing their opinions, active in group work, and capable of socializing. Thus, the application of the Small Group Discussion method can increase activity in learning Arabic.